Association of Serum Malondialdehyde and C-reactive Protein Levels with Exacerbations of Chronic Obstructive Pulmonary Disease - Kharazmi, Amir B.; Abedini, Atefeh; Kiani, Arda; Barouti, Shahriar; Mohammadi, Shooka (Current Respiratory Medicine Reviews, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is related to oxidant/antioxidant imbalance and systemic inflammation. Objective: This study was conducted to evaluate associations of serum levels of C-reactive protein (CRP) and malondialdehyde (MDA) with the severity and exacerbations of COPD. Methods: A matched case-control study was performed among 200 COPD patients (100 cases and 100 controls) who were referred to Masih Daneshvari Hospital in Tehran, Iran. Cases were exacerbators with equal to or greater than two ambulatory exacerbations or one hospitalization; controls were non-exacerbators who had one/no ambulatory exacerbation during the preceding 12 months. Blood samples were collected for CRP, MDA, and erythrocyte sedimentation rate (ESR) analysis. In addition, spirometry, the COPD assessment test (CAT) score, the modified Medical Research Council (mMRC) dyspnea scale, and the BODEx index were applied. Results: The mean (SD) age of the patients was 65.31 (8.46) years. Those with exacerbations had significantly lower FEV1 and higher CRP, MDA, ESR, BMI, BODEx index, CAT, and mMRC scores compared to non-exacerbators. There were significant differences in CRP, MDA, ESR, FVC, FEV1, FEV1/FVC, BMI, BODEx index, mMRC, and CAT scores between the GOLD group. Moreover, multivariate analysis showed that higher levels of CRP (OR=0.61, p=0.023), MDA (OR=0.28, p=0.001), ESR (OR=0.86, p=0.029), CAT score (OR=0.84, p=0.012), BODEx index (OR=0.89, p <0.001), BMI (OR=0.42, p <0.001), and lower FEV1% (OR=0.77, p <0.001) were independent risk factors for frequent exacerbations. Conclusion: In conclusion, elevated serum MDA and CRP levels in combination may serve as prognostic indicators of the severity and exacerbation of COPD.
Keywords: CRP